Implementasi Pengelolaan Badan Usaha Milik Desa (BUMDesa) Jatimakmur Dalam Peningkatan Pendapatan Asli Desa (PADes) Di Desa Jatirejoyoso - Hasbullah Bin Abdullah (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2021)
The purpose of this study was to determine the implementation of Jatimakmur Village Owned Enterprise Management (BUMDes) in increasing Village Original Income (PADes) in Jatirejoyoso Village. The method used by researchers in this study is descriptive research with a qualitative approach. The data used in this study are primary data and secondary data. Primary data is data from interviews with respondents related to the implementation of Jatimakmur BUMDes management in increasing Jatirejoyoso Village Original Income. According to Article 1 Number (6) of Law Number 6 of 2014 concerning Villages, it is written that Village-Owned Enterprises, hereinafter referred to as BUMDes, are business entities whose entire or most of the capital is owned by separate villages to manage assets, services, and other businesses. for the welfare of rural communities. Then, amended through the Job Creation Act no. 11 of 2020 Article 117 and Article 185 explain that BUMDes is a legal entity established by villages and/or together with villages to manage businesses, assets, develop investment and productivity, provide services, and/or other businesses for the greatest welfare. public. Village Original Income (PADes) is all efforts made by the village government to support the implementation of Village Government in the context of implementing Village autonomy (Law Number 6 of 2014 concerning Villages Article 71). According to the explanation of Law Number 6 of 2014 Article 72 paragraph (1) letter a what is meant by